2018
DOI: 10.1007/s11103-018-0709-x
|View full text |Cite
|
Sign up to set email alerts
|

Potential high-frequency off-target mutagenesis induced by CRISPR/Cas9 in Arabidopsis and its prevention

Abstract: Key messageWe present novel observations of high-specificity SpCas9 variants, sgRNA expression strategies based on mutant sgRNA scaffold and tRNA processing system, and CRISPR/Cas9-mediated T-DNA integrations.AbstractSpecificity of CRISPR/Cas9 tools has been a major concern along with the reports of their successful applications. We report unexpected observations of high frequency off-target mutagenesis induced by CRISPR/Cas9 in T1 Arabidopsis mutants although the sgRNA was predicted to have a high specificity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(107 citation statements)
references
References 44 publications
1
92
0
Order By: Relevance
“…4). The tRNA-sgRNA system, originally described by Xie et al (2015) in rice, was later successfully applied in wheat [35] and Arabidopsis [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). The tRNA-sgRNA system, originally described by Xie et al (2015) in rice, was later successfully applied in wheat [35] and Arabidopsis [36].…”
Section: Discussionmentioning
confidence: 99%
“…The tRNA-gRNA system for Cas9 multiplexing has proven to work in monocots [6,35] as well as in dicots [36]. In dicots, it was shown that fusing tRNAs with the optimised sgRNA backbone [39] increased editing efficiencies [36]. In monocots however, only the classic sgRNA backbone [40] was so far used in tRNA-sgRNA arrays.…”
Section: Discussionmentioning
confidence: 99%
“…3; Supplementary table 1), indicating that sgRNA against PLT2 was disassociated from tRNA processing and guiding Cas9p to cleave PLT2 . It has recently been reported that efficient genome editing could be achieved by fusing tRNA to a mutant sgRNA scaffold but not the wild type sgRNA scaffold in Arabidopsis 36 . However, in our hands wild type sgRNA scaffold and tRNA fusion worked well.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, sequence specificity is achieved by a short region (19–22 nt) in the gRNA that is complementary to the host target sequence and next to a 3‐ to 6‐nt protospacer adjacent motif (PAM) sequence (Table ; Jinek et al ). Off‐target mutations can occur at undesired sites that have mismatches distal to the PAM (Zhang et al ). However, several bioinformatic tools are now available to predict off‐target activity based on the gRNA(s) and Cas used, which can subsequently be screened for during analysis (reviewed in Zischewski et al ).…”
Section: Crispr/cas Gene Editing In Actionmentioning
confidence: 99%